The fundamental principles of implementing software for highway tracing using the flexible bracelet method - Musiienko, I. V.; Мусієнко, Ігор Володимирович (Харківський національний автомобільно-дорожній університет, 2025)
The article under consideration reveals the necessity of developing and implementing optimization algorithms for the automated laying of road axes. The state of the issue is reviewed, and the previously proposed computer-system approach in highway design is discussed, as well as the method of laying the road axis with maximum radii and the flexible bracelet method. The latter was created for the realization of the computer-system approach in highway design. The article is devoted to the basics of software implementation of the flexible bracelet method. The creation of a functional that facilitates the construction of a flexible bracelet of any complexity, with links that can be rotated relative to the joints, and the subsequent superimposition of this construction on a topographic map, is a key contribution of this article.
Основи програмної реалізації трасування автомобільних доріг за допомогою методу гнучкого браслета
Keywords: highway axis design; computer-aided design; flexible bracelet method.; гнучкий браслет; трасування доріг; автоматизоване проєктування; CAD; оптимізація; геометричні обмеження; 625.721 : 004.94; 10.30977/BUL.2219-5548.2025.108.0.257